Analisis Kapasitas Sistem Saluran Drainase Di Perumahan Dramaga Cantik 2 Kabupaten Bogor - Qintana, Muhammad Raka; Pandjaitan, Nora H; Sutoyo, Sutoyo (Departemen Teknik Sipil dan Lingkungan IPB, 2019)
Bogor is a city with a high rainfall. Bogor has the average monthly rainfall of 267.3 mm with an average of 16 days of rain per month. This research purpose are to identify the condition of the existing drainage channels and to analyze the magnitude of runoff discharge compliance with existing drainage channels capacity. This research was conducted from May to August 2017 in Dramaga Cantik 2, Bogor, West Java, were analyzed using EPA SWMM 5.1. Based on the rainfall data processing of Dramaga area, Bogor, this research used distribution method of Log Pearson III. The result showed that maximum rainfall was 129.722 mm. The result of EPA SWMM 5.1. simulation showed that drainage channel capacity could accommodate the runoff, but channel C24 was overflow. It was suggested to improved channel width to 0.42 m with cost of Rp 2,368,393.00.Keyword: drainage channel capacity, EPA SWMM 5.1, rainfall, runoff